2022
DOI: 10.1002/ajoc.202200336
|View full text |Cite
|
Sign up to set email alerts
|

In‐catalyzed Transfer Hydrogenation of Azobenzenes to Hydrazobenzenes with Hydrosilanes

Abstract: A novel reducing system, In(OTf) 3 /PhSiH 3 , was developed, which smoothly and effectively hydrogenates a variety of azobenzenes to hydrazobenzenes. Azobenzenes with diverse functional groups were reduced to their corresponding hydrazobenzenes in high yields. The catalytic method utilized is simple and operates under exceedingly mild conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Over the last few years, organic photochemical synthesis has become a powerful tool to avoid or reduce the use of environmentally harmful metal reagents in conventional synthesis. 9 For example, Sudo et al reported the photocatalytic reductive coupling of imines using perylene as the photosensitizer and trialkylamine as the reducing agent. 10 Rueping's group used iridium photosensitizers to achieve visible light-mediated photoinduced catalytic reductive coupling of imines and direct coupling of imine–aniline and aldehyde–aniline to access a wide range of substrates under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Over the last few years, organic photochemical synthesis has become a powerful tool to avoid or reduce the use of environmentally harmful metal reagents in conventional synthesis. 9 For example, Sudo et al reported the photocatalytic reductive coupling of imines using perylene as the photosensitizer and trialkylamine as the reducing agent. 10 Rueping's group used iridium photosensitizers to achieve visible light-mediated photoinduced catalytic reductive coupling of imines and direct coupling of imine–aniline and aldehyde–aniline to access a wide range of substrates under mild reaction conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the catalytic reduction of azobenzenes has been pursued by different groups. In this respect, the combination of an appropriate catalyst and nonmetallic reducing reagents such as hydrazine hydrate (N 2 H 4 ·H 2 O) and boranes (NH 3 ·BH 3 , B 2 pin 2 , and HBpin) was widely explored (Scheme B). More recently, the transition-metal-catalyzed hydrogenation of azobenzenes under Pd/C, Mn­(I), and Ru­(II) was reported by the Balaraman, Rueping, and Xu groups .…”
Section: Introductionmentioning
confidence: 99%